Взаимодействие студентов-мигрантов в поликультурной образовательной среде - Маслова, Татьяна (Զանգակ հրատ.)
A migrant student is a person who commits a territorial movement between settlements of one or more administrative-territorial units in order to obtain professional education. The article investigates the problems of interaction of migrant students in the new multicultural educational environment and draws some conclusions about preventing and overcoming cultural shock. Հոդվածում ներկայացված է բազմամշակութային կրթական միջավայրի առանձնահատկությունները, որտեղ հեղինակը մանրամասնել է ուսանող միգրանտների փոխշփումների, հաղորդակցման ու համագործակցության ծավալման առանձնահատկությունների և մասնավորապես փոխգործունեության հետ կապված հիմնախնդիրները:
Keywords: Поликультурное образование